Homework Help

Solve the following simultaneous equations. x + 3y = 2 , 2x + 8y = 6  

user profile pic

tonyah995 | Student, Undergraduate | Salutatorian

Posted February 12, 2011 at 10:00 PM via web

dislike 1 like

Solve the following simultaneous equations.

x + 3y = 2 , 2x + 8y = 6

 

4 Answers | Add Yours

user profile pic

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted February 12, 2011 at 10:10 PM (Answer #1)

dislike 1 like

We have to solve the following set of simultaneous equations:

x + 3y = 2 ...(1)

2x + 8y = 6 ...(2)

2*(1) - (2)

=> 2x + 6y - 2x - 8y = 4 - 6

=> -2y = -2

=> y = -2/-2

=> y = 1

substitute in (1)

x + 3 = 2

=> x = 2 - 3

=> x = -1

We get x = -1 and y = 1

user profile pic

giorgiana1976 | College Teacher | Valedictorian

Posted February 12, 2011 at 11:54 PM (Answer #2)

dislike 0 like

We'll solve the system using substitution method and we'll write x from the 1st equation, with respect to y:

x = 2 - 3y

We'll substitute x in the 2nd equation:

2(2 - 3y) + 8y = 6

We'll remove the brackets:

4 - 6y + 8y = 6

We'll combine like terms:

2y = 6 - 4

2y = 2

y  = 1

We'll substitute y in the first equation:

x + 3 = 2

x = 2  - 3

x = -1

The solution of the system is represented by the pair (-1 ; 1).

user profile pic

atyourservice | TA , Grade 10 | Valedictorian

Posted June 30, 2014 at 12:38 PM (Answer #3)

dislike 0 like

x + 3y = 2 

x = 2 - 3y

plug it in as x into the other equation:

2(2 - 3y) + 8y = 6

4 - 6y + 8y = 6

bring like terms to the same side:

-6y + 8y = 6 - 4

combine:

2y = 2

divide by 2

  • y = 1

now plug that into any of the problems:

x + 3(1) = 2 

x + 3 = 2

subtract 3

x = 2 - 3

  • x = -1

(-1 , 1)

user profile pic

givingiswinning | Student, Grade 10 | Valedictorian

Posted August 15, 2014 at 11:32 PM (Answer #4)

dislike 0 like

x + 3y = 2 

x = 2 - 3y

plug it in as x into the other equation:

2(2 - 3y) + 8y = 6

4 - 6y + 8y = 6

bring like terms to the same side:

-6y + 8y = 6 - 4

combine:

2y = 2

divide by 2

y = 1

x + 3(1) = 2 

x + 3 = 2

subtract 3

x = 2 - 3

x = -1
(-1 , 1)
 
 

Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes